Advances in Soliton Crystal Microcombs - Zhihui Liu; Haoran Zhang; Yuhang Song; Xiaotian Zhu; Caitlin E. Murray; Yunping Bai; Mengxi Tan; Sai T. Chu; David J. Moss; Xingyuan Xu; Kun Xu (Photonics)
Soliton crystal microcombs, as a new type of Kerr frequency comb, offer advantages such as higher energy conversion efficiency and a simpler generation mechanism compared to those of traditional soliton microcombs. They have a wide range of applications in fields like microwave photonics, ultra-high-speed optical communication, and photonic neural networks. In this review, we discuss the recent developments regarding soliton crystal microcombs and analyze the advantages and disadvantages of generating soliton crystal microcombs utilizing different mechanisms. First, we briefly introduce the numerical model of optical frequency combs. Then, we introduce the generation schemes for soliton crystal microcombs based on various mechanisms, such as utilizing an avoided mode crossing, harmonic modulation, bi-chromatic pumping, and the use of saturable absorbers. Finally, we discuss the progress of research on soliton crystal microcombs in the fields of microwave photonics, optical communication, and photonic neural networks. We also discuss the challenges and perspectives regarding soliton crystal microcombs.